Facilitating the housing bargaining with the help of the bargaining decision support system - Urbanavičienė, Vita; Kaklauskas, Artūras; Zavadskas, Edmundas Kazimieras; Šliogerienė, Jūratė; Naimavičienė, Jurga; Vatin, Nikolay Ivanovich (International Journal of Strategic Property Management, 2014)
More than 90 percent home buyers today rely on the Internet as one of their primary research sources and real estate related searches continually grows. Internet helps buyers to find and select bigger number of right homes for sale in a shorter time, so provides more alternatives for bargaining. The bargaining is an inseparable part of the home buying and selling process. However, housing bargaining mostly is conducted face-to face, so there is a growing need for facilitating the housing bargaining and conducting such bargaining on the Web with the help of the systems. The article describes the developed Real-Time Housing Multiple Criteria Bargaining Decision Support System, based on multiple-criteria mathematical methods, which helps to improve the efficiency of bargaining through the following functions: search for housing alternatives; formulation of the initial comparative table of alternatives; multiple criteria analysis of housing alternatives and negotiation tactics; determination of the most useful home option for buying; presentation of recommendations and real-time determination of a home's market value; e-bargaining using templates of bargaining e-mails generated by the system.First Publish Online: 18 Sep 2014